Ultrastruktur Biji Kacang Tanah Pada Beberapa Tahap Pengolahan - B.A. Susila Santoso; Yulianto Yulianto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1992)
Study on edible peanut (Arachishypogaea L.) seed ultrastructure related to peanut processing stages were conducted at Sukamandi Research Institute for Food Crops. Macan (peanut variety)was dried ,until its moisture content was 6-7%. The peanut seeds were pressed hidraulically at 300 kg/cm2 for 1.5minutes to obtain partially defatted peanut (kacang tanah lemah rendah, KTLR). The pressed peanut (KTLR) was expanded in water or sauce water for 30 minutes to make partially defatted peanut expanded (kacang tanah lernak rendan rekonstitui,KTLRr). The content of protein and oil of the fried products were evaluated, and their ultrastructure were observed under a scanning electron microscope. Hydraulically pressing stages caused the peanut protein content increase from 26,5 to 43.1% and oil content decrease from 42.2 to 26.2%.